Gendered perceptions of police conduct: public reactions to officer gender in a traffic stop scenario - Navarro, John C; Malvitz, Sierra A.; Hansen, Michael A. (emerald insight, 2025)
Purpose
This study aims to explore the influence of police officer gender on public perceptions during an interaction between an officer and a citizen suspected of driving under the influence.
Design/methodology/approach
Using an experimental survey with a sample of 1,193 USA adults, participants were randomly assigned to read a hypothetical news story in which the officer’s gender was manipulated (Control: no gender, T1: male, and T2: female). The study sought to determine whether officer gender affected evaluations of the officer’s conduct, including appropriateness, reasonableness, the need for backup, and the potential for de-escalation.
Findings
While no significant differences were found for most evaluations, respondents were significantly more likely to recommend that a female officer call for backup, indicating that gendered expectations may shape perceptions of when additional support is needed during conflict. The findings suggest that officer gender does not significantly affect broader evaluations of police conduct in less contentious scenarios.
Research limitations/implications
Manipulation checks of officer gender should be analyzed as misidentification may reveal patterns of gender biases in policing perceptions.
Practical implications
Police training and policy should address gender biases in perceptions of officers and promote greater diversity and inclusion, especially as officer gender may not significantly shape public perceptions of police-citizen interactions.
Social implications
Media portrayals may reinforce perceptions of women officers needing greater assistance in handling situations.
Originality/value
The study relies on a nationally representative sample, testing public perceptions of a different but everyday police-citizen interaction, specifically a traffic stop scenario, to assess whether officer gender influences evaluations of procedural justice and decision-making. Further, the study examines respondents who misidentified the officer’s gender to uncover patterns in these misidentifications.